The Effect of Exenatide on Thyroid-Stimulating Hormone and Thyroid Volume. Issue 6 (15th December 2019) - Sencar, Muhammed Erkam; Sakiz, Davut; Calapkulu, Murat; Hepsen, Sema; Kizilgul, Muhammed; Ozturk, Ilknur Unsal; Ucan, Bekir; Bayram, Murat; Cagir, Busra Betul; Akin, Safak; Ozbek, Mustafa; Cakal, Erman
Abstract : Objective: Glucagon-like peptide-1 (GLP-1) analogues are now widely used for the treatment of type 2 diabetes mellitus (DM). Many binding sites for GLP-1 have been demonstrated in the specific tissue compartments of organs including the brain and thyroid. The aim of this study was to investigate the effect of exenatide treatment on thyroid-stimulating hormone (TSH) and thyroid volume in diabetic patients without thyroid disease. Material and Methods: The study included 46 diabetic patients without thyroid disease who were receiving exenatide treatment. Comparisons were made of total thyroid volume and serum concentrations of TSH at baseline and after 6 months of follow-up. Results: Of the 46 patients, 13 were excluded from the study, as they were unable to complete the treatment or left the follow-up process. After 6 months of exenatide treatment, the serum TSH concentration decreased significantly (from 2.3 [0.7–5.4] to 1.8 mIU/L [0.3–4.2], p = 0.007). There were no significant differences in thyroid volume (11.6 ± 9.0 vs. 12.1 ± 8.8 cm 3, p = 0.19), free thyroxine (fT4), free tri-iodothyronine (fT3), and calcitonin levels before and after treatment. Thyroid volume was not affected by decreased TSH level ( p : = 0.141) or a reduction in body mass index (BMI) ( p > 0.05), and no correlation was detected between variation in TSH level and change in BMI ( p > 0.05). Conclusions: Exenatide treatment for 6 months significantly decreased serum TSH concentration but did not affect thyroid volume in diabetic patients without thyroid disease.